Freeze! Financial sanctions and bank responses - Stefan Goldbach; Matthias Efing; Volker Nitsch (ZBW - Leibniz-Informationszentrum Wirtschaft, 2019)
We study the effects of financial sanctions on cross-border credit supply. Using a differences-in-differences approach to analyze eleven sanctions episodes between 2002 and 2015, we find that banks located in Germany reduce their positions in countries with sanctioned entities by 38%. The average German branch or subsidiary located outside Germany does not adjust its positions after the imposition of sanctions. For affiliated banks located in countries with low financial standards, we even observe a relative increase in credit supply. These effects are stronger if sanctions are only imposed by EU member states and not by the entire UN.
Keywords: F51; G18; G28; G38; K33; 330; financial sanctions; law and finance; cross-border lending; international banking